Epigallocatechin-3-gallate enhances clearance of phosphorylated tau in primary neurons. (January 2016) - Chesser, Adrianne S.; Ganeshan, Veena; Yang, Jonathan; Johnson, Gail V. W.
Abstract : Objectives: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by intracellular accumulations of phosphorylated forms of the microtubule binding protein tau. This study aimed to explore a novel mechanism for enhancing the clearance of these pathological tau species using the green tea flavonoid epigallocatechin-3-gallate (EGCG). EGCG is a potent antioxidant and an activator of the Nrf2 transcriptional pathway. Nrf2 activators including EGCG have shown promise in mitigating amyloid pathology in vitro and in vivo . This study assessed whether EGCG could also alter tau clearance. Methods: Rat primary cortical neuron cultures were treated on day in vitro 8 with EGCG and analyzed for changes in gene and protein expression using luciferase assay, q-PCR, and western blotting. Results: EGCG treatment led to a significant decrease in the protein levels of three AD-relevant phospho-tau epitopes. Unexpectedly, EGCG does not appear to be facilitating this effect through the Nrf2 pathway or by increasing autophagy in general. However, EGCG did significantly increase mRNA expression of the key autophagy adaptor proteins NDP52 and p62. Discussion: In this study, we show that EGCG enhances the clearance of AD-relevant phosphorylated tau species in primary neurons. Interestingly, this result appears to be independent of both Nrf2 activation and enhanced autophagy – two previously reported mechanisms of phytochemical-induced tau clearance. EGCG did significantly increase expression of two autophagy adaptor proteins. Taken together, these results demonstrate that EGCG has the ability to increase the clearance of phosphorylated tau species in a highly specific manner, likely through increasing adaptor protein expression.